The Impacts of Bushmeat Exploitations on the Conservation of Wildlife in Nigeria (2021)
This paper examines the impacts of exploitation of wild animals as bush-meat on the conservation of wildlife in Nigeria. This study was carried out in Six (6) States of Nigeria namely Abia; Bauchi; Edo; Kogi; Ondo; and Zamfara State which represents the six geo-political zones of Nigeria namely South-East; NorthEast; North-Central; South-West; South-South; and North-West in the country. Data were collected from two Local Government Areas (LGAs) which were randomly selected from each of the six states making twelve LGAs within the Study Area using structured questionnaire; oral interview of respondents; and visual observation. The data were analyzed using descriptive statistics involving tables and figures. Two-factor without replication Analysis of Variance (ANOVA) was used to analyze the differences in the wildlife species mostly hunted. The results revealed that Twenty-Six (26) wild animal species were recorded as bush-meat in the Study Area. Eleven percent (11.0%) of the 26 species of bush-meat were recorded in Abia State; 23.0% in Bauchi State; 11.0% in Edo State; 17.0% in Kogi State; 21.0% in Ondo State; and 17.0% in Zamfara state. The wild animals’ exploitation rate shows that the month of March had the highest exploitation rate (25.0%) while the month of September has the lowest extraction rate (8.0%). Most of the respondents (80.3%) in the Study Area carried out hunting activities for income generation while 19.7% respondents carried out hunting activities for food. The results of ANOVA two-factor without replication of the hunted wild animals in the Study Area indicated that there were significant differences (P-value < 0.05 and F-calculated > F-critical) in the wild animal species mostly hunted. This is a pointer to the fact that there will be negative impact of wild animal exploitation on the conservation of wildlife, if nothing is done to reduce hunting activities for income generation.